False Banana (Enset Ventricosum) Fibers: An Emerging Natural Fiber with Distinct Properties, Promising Potentials, Challenges and Future Prospects–A Critical Review - Bekinew Kitaw Dejene (Journal of Natural Fibers)
Current research and design initiatives are cautiously focused on the use of natural fibers from agricultural waste, as they can generate financial gains, improve crop sustainability, and effectively address environmental issues. In Ethiopia, an estimated 100–million Enset plants are harvested annually for their starchy food, providing 20% of the population. This process generates approximately 150,000 tons of Enset fiber, which researchers are actively investigating as a promising and eco-friendly fiber source. Fibers from the Enset plant have been investigated for their potential use in various applications, particularly as materials for cellulosic nanocrystals, paper, and composites production. However, the potential of Enset fiber remains largely untapped due to the limited understanding of its properties, and the inconsistencies in the data reported by previous studies regarding its chemical, physical, mechanical, and thermal properties. Therefore, it is crucial to organize the data for researchers and manufacturers to make informed decisions regarding future studies and applications of this fiber. This review discusses recent research on the unique properties of Enset fibers, their potential as green composites, and their potential for paper and cellulosic nanocrystals as an alternative to natural fibers. The review also unveils the challenges of Enset fibers in advanced applications and suggests future research avenues.